Optineurin knock-out forms TDP-43 aggregates to regulate TDP-43 protein levels despite autophagic up-regulation and aberrant TDP-43 expression - Yuta Maetani; Takashi Kurashige; Yui Tada; Kodai Kume; Tomoaki Watanabe; Yusuke Sotomaru; Koji Yamanaka; Hirofumi Maruyama; Hideshi Kawakami (Neuroscience Research)
Optineurin is a causative gene of amyotrophic lateral sclerosis (ALS) and has many roles in processes such as autophagy and inflammation. However, it is unclear how optineurin causes ALS. Optineurin knock-out (Optn-KO) mice, which have been generated by several researchers, exhibit motor neuron degeneration and TDP-43 aggregates, but no motor deficits. Motor dysfunction in ALS model mice is associated with TDP-43 in the spinal cord. We bred Optn-KO mice with TDP-43 overexpression transgenic mice and evaluated whether increased TDP-43 protein causes motor deficits and whether Optn-KO affects TDP-43 protein level. Optn-KO mice had spinal TDP-43 protein levels and motor function comparable to wild-type mice, and TDP-43-transgenic (TDP-43-tg) mice resulted in motor dysfunction and early death. However, double-mutant TDP-43-tg / Optn-KO mice had lower TDP-43 protein levels than TDP-43-tg mice at 18 months age, and showed inhibition of the TBK1-optinerurin autophagic pathway with aging. Furthermore, Optn-KO caused TDP-43-positive cytoplasmic aggregates. TDP-43 overexpression by itself induced spinal microgliosis, but Optn-KO suppressed that microgliosis. Finally, we showed that Optn-KO mice could not exhibit behavioral dysfunction because TDP-43 protein levels were not elevated despite autophagy inhibition. Thus, downregulation of Optn may suppress TDP-43 toxicity by regulating its abundance through aggregate formation.